PB2-588 V promotes the mammalian adaptation of H10N8, H7N9 and H9N2 avian influenza viruses - Xiao, C. C.; Ma, Wenjun; Sun, N.; Huang, L. H.; Li, Y. L.; Zeng, Z. Y.; Wen, Y. J.; Zhang, Z. Y.; Li, H. A.; Li, Q.; Yu, Y. D.; Zheng, Y.; et al. (My University, 2016)
Human infections with avian influenza H7N9 or H10N8 viruses have been reported in China, raising concerns that they might cause human epidemics and pandemics. However, how these viruses adapt to mammalian hosts is unclear. Here we show that besides the commonly recognized viral polymerase subunit PB2 residue 627 K, other residues including 87E, 292 V, 340 K, 588 V, 648 V, and 676 M in PB2 also play critical roles in mammalian adaptation of the H10N8 virus. The avian-origin H10N8, H7N9, and H9N2 viruses harboring PB2-588V exhibited higher polymerase activity, more efficient replication in mammalian and avian cells, and higher virulence in mice when compared to viruses with PB2-588 A. Analyses of available PB2 sequences showed that the proportion of avian H9N2 or human H7N9 influenza isolates bearing PB2-588 V has increased significantly since 2013. Taken together, our results suggest that the substitution PB2-A588V may be a new strategy for an avian influenza virus to adapt mammalian hosts.
Citation: Xiao, C. C., Ma, W. J., Sun, N., Huang, L. H., Li, Y. L., Zeng, Z. Y., . . . Liao, M. (2016). PB2-588 V promotes the mammalian adaptation of H10N8, H7N9 and H9N2 avian influenza viruses. Scientific Reports, 6, 13. doi:10.1038/srep19474
Additional Authors: Zhang, X.;Ning, Z. Y.;Qi, W. B.;Liao, M.
Keywords: A H5N1 Virus; Amino-Acid Changes; Receptor-Binding; Human Infection; Molecular-Basis; Cell Tropism